Adsorption of Paracetamol and Acetylsalicylic Acid onto Commercial Activated Carbons - Sabina Beninati; Domenica Semeraro; Marina Mastragostino (Adsorption Science & Technology)
The adsorption of paracetamol (PAR) and acetylsalicylic acid (ASA) onto high-surface-area, commercial activated carbons was investigated at 26°C via adsorption isotherms at different pH values, including pH 1.5 to simulate conditions existing in the stomach. A wide-ranging characterization of the carbons, including analysis of their morphology and surface chemistry, was undertaken, with the actual surface areas of the carbons available for PAR and ASA adsorption being estimated by taking the molecular sizes of the drugs into account. This provided an understanding of the differences in the drug adsorption behaviour of the carbons.